Prognostic Factors for Cognitive Recovery Beyond Early Poststroke Cognitive Impairment (PSCI): A Prospective Cohort Study of Spontaneous Intracerebral Hemorrhage - Gong, Li; Gu, Yongzhe; Yu, Qiuyue; Wang, Haichao; Zhu, Xiaoping; Dong, Qiong; Xu, Rong; Zhao, Yanxin; Liu, Xueyuan (Frontiers in Neurology, 2020)
Background: Post-stroke cognitive impairment (PSCI) has been increasingly recognized in patients, but some stroke survivors appear to show cognitive improvement beyond the acute stage. The risk factors associated with cognitive recovery after spontaneous intracerebral hemorrhage (ICH) onset have not yet been sufficiently investigated in prospective studies. Objective: We aimed to identify the trajectory of post-ICH cognitive impairment and the association of potential prognostic factors with follow-up cognitive recovery beyond early PSCI. Methods: In this stroke center-based cohort study, 141 consecutive dementia-free patients with spontaneous ICH were included and underwent Montreal Cognitive Assessment (MoCA) evaluation for cognitive function at baseline (within 2 weeks of ICH onset) and the shortened MoCA (short-MoCA) at a 6-month follow-up. To explore the prognostic factors associated with trajectory of cognition after an ICH onset, we adjusted for demographic and vascular risk factors,using multivariate logistic regression analysis. Results: Of the 141 ICH patients, approximately three quarters (106/141) were diagnosed with early PSCI (MoCA score<26) within 2 weeks of ICH onset. The multiple logistic regression indicated independent positive associations between risk of early PSCI and dominant-hemisphere hemorrhage (OR: 8.845 [3.347-23.371]; P < 0.001), mean corpuscular volume (MCV) (OR: 1.079 [1.002-1.162]; P = 0.043), admission systolic blood pressure (sBP) (OR: 1.021 [1.005-1.038]; P = 0.012). Furthermore, 36% (33/90) of ICH survivors who had early PSCI exhibited cognitive recovery at the 6-month follow-up. After examing potential predictors through multiple linear regression based on stepwise, there were independent negative associations between cognitive recovery and dominant hemisphere hemorrhage (OR: 6.955. [1.604-30.162]; P < 0.01), lobar ICH (OR: 8.363 [1.479-47.290]; P = 0.016), years of education ≤ 9 (OR: 5.145 [1.254-21.105]; P = 0.023), and MCV (OR: 1.660 [1.171-2.354]; P = 0.004). Baseline cognitive performance in the domains of visuospatial/executive function, attention, orientation, and language showed positive correlations with cognitive improvement (P < 0.05). Conclusion: In this cohort study of dementia-free survivors of ICH, our results show that one in three early PSCI survivors exhibit cognitive recovery, in relation to dominant-hemisphere hematoma, lobar ICH, educational history, and MCV levels. Future clinical trials including ICH survivors with cognitive dysfunction should assess these factors.